I (non)luoghi del mito. Sulle strade del grande ciclismo - Perissinotto, Alessandro (Eracle. Journal of Sport and Social Sciences, 2019)
Just as cathedrals speak of religion even when mass is over, large sports facilities speak of sport, even if the game or competition is over. Arenas, ski jumping boards, sports halls are places of sport and, as places, they are both cultural heritageand tourist attraction. On the contrary, the road, a space of transit and not of permanence, is a non- place by definition; but what happens to this non-place when it becomes the seat of the cycling myth? What happens to this “identityless” space (according to Augé’s definition) when it is covered with words praising the various champions and filled with fans who, like real sports tourists, camp and live on the road? What happens to the street when, by virtue of sports mythology, it becomes the object of pictorial, literary, photographic and musical representations? This short essay aims to investigate the role of cycling in the transformation of the road from a non-practical place to a place fully inscribed within the material and immaterial heritage of European culture.